SEASONAL IMPACT OF HARVESTING ON THE FRESHNESS ANDQUALITY OF GILTHEAD SEABREAM MEAT (Sparus aurata Linnaeus, 1758) - Lepara, Dino; Muhamedagić, Samir (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
In order to determine the impact of seasonal and stunning ways to maintain the freshness and quality of the gilthead seabream meat for consumption, 50 samples in two seasons (summer and winter) were randomly caught in the Bay of Neum using two stunning ways: using ice/sea water mixture (group I) and using anesthetic (group II). After stunning, number of muscle contractions, blood lactate concentration, temperature and pH of fish meat were measured. During laboratory analysis, trend values of pH and temperature were continued. The analysis also included the measurement of morphometric values, determination of the chemical composition of fish meat and carrying out the sensory analysis (QIM – Quality Index Method). The results showed that analyzed specimens were with uniform morphometric measures, without statistically significant differences between groups and seasons. According to a determined chemical composition, protein content was 17.7% (in summer period) and 18.5% (in winter period), moisture content was 70.2% (summer) and 78.0% (winter), and crude fat was 3.98% (summer) and 1.17% (winter). A statistically significant difference between seasons occurred at the moisture content, and especially for fat content. Temperatures are slightly down during the analysis with statistical difference between seasons every day, except day 11th. Readings of pH during analysis were 6.41 to 7.12 with a statistically significant difference between seasons at day 7 and 9. Based on the lactate content, it can be concluded that the fish group I (anesthetic) from the winter season survived stress levels higher than all other groups. Higher average number of muscle contraction after stunning was recorded in the fishes from group II (2.0) than in fish from group I (0.54). QIM values, as expected, had constant increase during testing (from 0.0 to 12.0), with significant differences between seasons for days 3, 7 and 11. Stunning methods, therefore, do not have an impact on maintaining the freshness and quality of gilthead seabream meat during storage, but the season of harvest has.